HAK WARIS ISTRI PEMBERI NAFKAH DALAM MAQASHID SYARI’AH: STUDI KASUS DI DESA ANCARAN - Mualim, Mualim; Ulviyah, Silvi Maryam (El 'Ailaah, 2024)
In reality, due to various factors including economic demands, it is often found that there is a family or household, not only the husband earns a living, but the wife also participates in earning a living to support his family as a female worker. There are even households where the wife works and is fully the breadwinner of the family while the husband is not working. This research also aims to determine the inheritance rights of wife primary breadwinner from husband who does not work in the provisions of the distribution of community inheritance in Ancaran Village. Kuningan Sub District, Kuningan Regency. The research method used is a qualitative method. This research includes the type of field research. Data collection techniques used are interviews and documentation. The research found that First that  in practice women workers who being wife primary breadwinner for. the husbands who does not work in Ancaran Village were still gaining inheritance rights from their husbands which was being inherited from their husbands’ ancestry. However, the amount of inheritance was varied among families. There is a wife who inherits the entire property left by her husband in the form of a house, and there is also a wife who inherits half of the property left by her husband because the husband has more than one wife. Second, according to Maqasid shari'ah, that the distribution of inheritance carried out by the people of Ancaran Village, Kuningan Sub District, Kuningan Regency to wives who being primary breadwinner for husbands who do not work is permissible in which the wife remains entitled to receive inheritance from the assets of her husband if there is approval from the family.